2021
DOI: 10.1007/s00066-020-01743-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumonia treated with ultra-low doses of radiotherapy (ULTRA-COVID study): a single institution report of two cases

Abstract: Introduction Since the outbreak of coronavirus disease 2019 (COVID-19) pandemic, healthcare systems have focused their efforts into finding a treatment to avoid the fatal outcomes of severe acute respiratory syndrome due to coronavirus-2 (SARS-CoV-2). Benefits and risks of systemic treatments remain unclear, with multiple clinical trials still ongoing. Radiotherapy could play a role in reducing the inflammatory response in the lungs and relieve life-threatening symptoms. Methods We designed a prospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Both patients experienced clinical improvement after LD-RT according to the increase in PaO 2 /FiO 2 ratio above 300 mm Hg as well as reduced dyspnea, asthenia and bilateral pulmonary infiltrative pattern, visible in the chest CT. In addition, the authors also report a decrease in inflammatory parameters, especially IL‑6 levels [ 26 ]. Del Castillo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients experienced clinical improvement after LD-RT according to the increase in PaO 2 /FiO 2 ratio above 300 mm Hg as well as reduced dyspnea, asthenia and bilateral pulmonary infiltrative pattern, visible in the chest CT. In addition, the authors also report a decrease in inflammatory parameters, especially IL‑6 levels [ 26 ]. Del Castillo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, delivering radiation therapy to hypoxic COVID-19 patients, who may have ARDS, could increase the risk of infection to staff and other patients if not enough safety measures are taken. However, current data indicate that the cancer risk associated with LDRT is scarce [28,40,41]. LDRT can affect the lung macrophages significantly at 0.5 and 1 Gy radiation doses.…”
Section: Discussionmentioning
confidence: 98%
“…In Figure 2, the sample sizes of the 9 clinical trials reviewed in this study are shown. The highest number of samples in any of the trials was 36 patients (Arenas et al [27]), while the lowest number of samples was only 2 (Moreno et al [28]). was 36 patients (Arenas et al [27]), while the lowest number of samples was only 2 (Moreno et al [28]).…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current studies related to COVID-19 have focused on epidemiology [ 20 ], the clinical course of the disease [ 21 ], the development and efficacy of vaccines [ 22 ], and infection control guidelines [ 23 ]. Some studies have reported psychological problems such as depression, anxiety, and fear, and have focused on the general public and on patients with autoimmune disease, cancer, and chronic disease [ 9 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%